The Influence of Culture and Art Management on the Healthy Development of Cultural Economy Industry under the Background of Sustainable Ecological Environment. (13th September 2022) - Xu, Jingyi; Wang, Jianxin; Liu, Qingyang; Xie, Ziyan; Seo Jae, Lee; Fiaidhi, Avera; Marcos, Elvan
Abstract : In the context of sustainable ecological environment, strengthening the scientific management of cultural industry can promote the rapid development of China's cultural industry and further promote the construction of spiritual civilization in China. Starting from culture and art management, this study expounds its position in the development of cultural economy industry and its impact on the development of cultural economy. Through two different methods of culture and art management and conventional management, this paper discusses the social and economic market benefit value, the demand for the healthy development of industry, and the impact of innovative cultural industry resources on the development of cultural industry. It can be concluded that culture and art management plays a certain role in promoting the healthy development of cultural economy industry; we should constantly sum up experience in the actual process of cultural industry management, find and solve problems in time, and gradually form a set of scientific and complete cultural and art management mode, which can realize the transformation of cultural and art industry faster and better promote the sustainable development of cultural economy and industry.